GOOGLE SLIDE DAN QUIZIZZ DALAM PENGEMBANGAN BUKU AJAR ELEKTRONIK INTERAKTIF (BAEI) MATEMATIKA - Arum Oktaliana Sari; Guntur Cahaya Kesuma; Dian Anggraini (Universitas Ahmad Dahlan, 2019)
This study aims to determine the attractiveness and feasibility and effectiveness of learning implemented using interactive electronic textbooks (BAEI) assisted by Google slides and quizizz on the matrix material. This research method is research and development (R&D) with the Borg and Gall development model. There are 10 stages in this development namely 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, 6) Product trial, 7) Product revision, 8) Trial usage. 9) Product revision, 10) Mass production. Data collection instruments used were questionnaires given to material experts and media experts to determine product viability, and were given to students to find out the attractiveness of products that had been developed as well as pretest and posttest test instruments. The results of data analysis obtained from material experts and media experts stated that teaching materials developed were feasible to be used by obtaining